Comparison of Short-Term Effects of Thrust Manipulation and Non-Thrust Mobilization at Cervicothoracic Junction in Mechanical Neck Pain - Saima Riaz, Atif Dustgir, Sana Hafeez, Rehan Ramzan Khan, Amman Ullah Nazir, Lal Gul Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to compare the effects of thrust manipulation and non-thrust mobilization at cervicothoracic junction in patients with mechanical neck pain. Methodology: The study design used was a Quasi-Experimental Trial conducted at Riphah Rehabilitation Center, Lahore. A sample size of 80 patients was taken using the non-probability convenient sampling technique. Patients were divided into two groups; group A was treated with Thrust manipulation while group B was treated with non-thrust mobilization at the cervicothoracic junction. The numeric pain rating scale (NPRS) and Universal Goniometer for Pain and Active Cervical Range of Motions (ACROM) were used. Patients were assessed at baseline (Pre-treatment), after the first treatment session (T1) and after the second treatment session (T2) after 48 hours. Data were analyzed by using SPSS 25. Results: Both groups showed significant improvement in pain and cervical range of motion. p-value of NPRS across the groups at pre-treatment time was p =0.86 and there was a significant difference at T1 & T2 with a p-value <0.05. The p-value for all cervical range of motions across the groups at pre-treatment time was > 0.05 and at post-treatment T1 & T2, all movements showed significant improvement in ROM with a p-value < 0.05. Conclusion: The study concludes that patients who received thrust manipulation at the cervicothoracic junction showed more significant short-term improvements in Pain and cervical range of motion than those who received non-thrust mobilization.